2020
DOI: 10.1186/s12887-020-1993-6
|View full text |Cite
|
Sign up to set email alerts
|

Muscle building supplement use in Australian adolescent boys: relationships with body image, weight lifting, and sports engagement

Abstract: Background: The extent and implications of muscle building protein supplement use among adolescents is relatively unknown. This study aimed to describe the prevalence of protein powder, creatine, and anabolic steroid use in a sample of 14-16 year-old boys in Australia, and the predictors of actual use, and intentions to use protein powder. Methods: Data were obtained from questionnaires with Australian adolescent boys aged 14-16 years from one independent boy's school in Melbourne (N = 237). Hierarchical linea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 33 publications
5
35
2
Order By: Relevance
“…Previous studies involving older adolescents in the general population found that up to 50% of boys (Hoffman et al, 2008;Eisenberg et al, 2012;Yager and McLean, 2020) and 20% of girls (Eisenberg et al, 2012) had ever used or used protein supplements during the past year. Meanwhile, the estimated overall proportion of general adolescents currently or previously using creatine supplements varies from 0.6 to 22.2% in boys and 0.6 to 3% in girls (Hoffman et al, 2008;Jagim et al, 2018;Miech et al, 2020;Yager and McLean, 2020). A recent study also found the 30-day prevalence of diet pill use in late adolescent boys and girls to be 1.5 and 1.7%, respectively (Miech et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies involving older adolescents in the general population found that up to 50% of boys (Hoffman et al, 2008;Eisenberg et al, 2012;Yager and McLean, 2020) and 20% of girls (Eisenberg et al, 2012) had ever used or used protein supplements during the past year. Meanwhile, the estimated overall proportion of general adolescents currently or previously using creatine supplements varies from 0.6 to 22.2% in boys and 0.6 to 3% in girls (Hoffman et al, 2008;Jagim et al, 2018;Miech et al, 2020;Yager and McLean, 2020). A recent study also found the 30-day prevalence of diet pill use in late adolescent boys and girls to be 1.5 and 1.7%, respectively (Miech et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors predict the use of protein and creatine supplements; among these is gender (Eisenberg et al, 2012). Ethnicity is suggested as another factor possibly explaining supplement use as a means of changing appearance (Eisenberg et al, 2012;Yager and McLean, 2020). Males of non-white ethnicities may experience more drive for muscularity (Swami, 2016) and body dissatisfaction and engage in more extreme body change strategies (Ricciardelli et al, 2007), while girls of some non-white ethnicities may experience less body dissatisfaction than white ethnicities (Kimber et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2012, results from a large subset ( n = 9417) of the National Health Interview Survey respondents indicated that 34.1% of the children or adolescents (mean age = ~11 years) reporting the use of dietary supplements to enhance sports performance, self-reported using creatine [ 23 ]. Most recently, in 2020 among a sample of Australian adolescent boys participating in a variety of sports, 8.4% of survey respondents reported current use of creatine and 25.7% reported the intent to use creatine or other dietary supplements in the near future [ 24 ]. Drive for muscularity, participating in weight training, and sport participation were strong predictors of supplement use [ 24 ].…”
Section: Prevalence Of Use Among Adolescentsmentioning
confidence: 99%
“…Most recently, in 2020 among a sample of Australian adolescent boys participating in a variety of sports, 8.4% of survey respondents reported current use of creatine and 25.7% reported the intent to use creatine or other dietary supplements in the near future [ 24 ]. Drive for muscularity, participating in weight training, and sport participation were strong predictors of supplement use [ 24 ]. It is important to note that there is an underlying concern that creatine use among adolescents may be a predictor of future illegal performance enhancing substance use.…”
Section: Prevalence Of Use Among Adolescentsmentioning
confidence: 99%